Ominous combination: COVID‐19 disease and Candida auris fungemia—Case report and review of the literature - Wael Goravey (14777254) (2023)
The identification of Candida auris fungemia in critically ill COVID-19 patients is detrimental, with huge implications on patient mortality and infectious control measures. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4827